Dialectics Revelation and Local Culture In The Tradition Of Mappanre Temme’ - Mustamin, Kamaruddin; Basri; Pamulang, Yunus (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This research aims to illustrate the integration between revelation and the local culture of the Sengkang city community. This research uses qualitative research with historical and anthropological approaches. The tradition of Mappanre Temme', also known as Mappanre Lebbe, is a traditional event of Khataman al-Qur'an conducted by the Bugis community as a form of worship because one of the family members has been ready or has finished reading the Holy Qur'an. Mappanre Temme' implemented maccera, which means as a thank you to ustadz (teacher) and hand over foodstuffs, and as a thank you to parents by slaughtering cows, goats, or chickens, depending on the level of community performance. Maccera can be livestock or foodstuffs such as rice, coconut, and bananas. The phenomenon of Mappanre Temme' is always hereditary by the people of Sengkang city, Wajo Regency, South Sulawesi is not only a culture that appears just like that. But this tradition arises because it is inspired by a hadith, as a form of practice from the companions of the Prophet, referred to as the mauquf hadith, which later developed into a tradition inherent in society.